2017
DOI: 10.1111/mmi.13877
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a newly identified d‐amino acid transaminase in Mycobacterium smegmatis complements glutamate racemase deletion

Abstract: Glutamate racemase (MurI) has been proposed as a target for anti-tuberculosis drug development based on the inability of ΔmurI mutants of Mycobacterium smegmatis to grow in the absence of d-glutamate. In this communication, we identify ΔmurI suppressor mutants that are detected during prolonged incubation. Whole genome sequencing of these ΔmurI suppressor mutants identified the presence of a SNP, located in the promoter region of MSMEG_5795. RT-qPCR and transcriptional fusion analyses revealed that the ΔmurI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…This suggested that either the expression or the biochemical activity of Dat is significantly different in this related bacterial species. This possibility is further supported by the recent characterisation of a similar enzyme in Mycobacterium smegmatis (33) where a Dat homologue was found to be able to compensate for null mutations is either the alanine racemase or the glutamate racemase null mutation. This property indicates that at least in M. smegmatis the enzymatic activity is bidirectional.…”
Section: Identification Of An Alternate D-alanine Synthetic Pathwaymentioning
confidence: 79%
See 1 more Smart Citation
“…This suggested that either the expression or the biochemical activity of Dat is significantly different in this related bacterial species. This possibility is further supported by the recent characterisation of a similar enzyme in Mycobacterium smegmatis (33) where a Dat homologue was found to be able to compensate for null mutations is either the alanine racemase or the glutamate racemase null mutation. This property indicates that at least in M. smegmatis the enzymatic activity is bidirectional.…”
Section: Identification Of An Alternate D-alanine Synthetic Pathwaymentioning
confidence: 79%
“…This integration of pathways seems to be supported by the characterisation of other bacterial species, where it has been shown that Listeria possess an equivalent Dat enzyme which seems to be fully capable of supplying the cells D-alanine in the absence of a functional alanine racemase (32), though the mutant strains do not exhibit L-alanine sensitivity. This idea is further supported by the characterisation of an enzyme comparable to Dat in Mycobacterium smegmatis showing that it can supply the cell with D-glutamate in the absence of the cognate racemase, MurI, as well as provide D-alanine in a strain deleted for the alanine racemase (33). Thus, it would seem this set of enzymes are well conserved in a diverse range of bacteria, but most obviously in Firmicutes and close relatives.…”
Section: Discussionmentioning
confidence: 91%
“…This is somewhat similar to the situation described in recently published research, where the murL gene was shown to be essential in M. smegmatis , and was a D-glutamate auxotroph. However, a point mutation in the promoter of another gene, Msmeg_5795 , which up-regulated the latter's expression, salvaged the auxotroph phenotype (Mortuza et al, 2018 ). How exactly the upregulation of glnR salvages the essentiality of glnA2 is not completely clear—this could be by upregulation of metabolic pathways bypassing the bottleneck created by glnA2 deletion, by inducing a gene with a redundant function or other possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Mycolicibacterium smegmatis is a rapid-growing bacterium and previously belonged to the genus Mycobacterium as basonym Mycobacterium smegmatis , to which many pathogenic mycobacteria, including M. tuberculosis , a causative agent of tuberculosis, and M. leprae , a causative agent of leprosy, are belonging (Gupta et al, 2018 ; Oren and Garrity, 2018 ). Therefore, M. smegmatis has been quite often used as substitute for M. tuberculosis or M. leprae in studies, especially in the field of molecular biology, and there are a number of literature (Bashiri and Baker, 2015 ; Brown-Elliott and Philley, 2017 ), more than 15 papers, listed only in 2018 (Angara et al, 2018 ; Burian and Thompson, 2018 ; Chandran et al, 2018 ; Chen et al, 2018 ; Dal Molin et al, 2018 ; Ghosh et al, 2018 ; Goins et al, 2018 ; Jesus et al, 2018 ; Kaur et al, 2018 ; Kumar et al, 2018 ; Lopez et al, 2018 ; Marney et al, 2018 ; Mortuza et al, 2018 ; Richards et al, 2018 ; Singh et al, 2018 ; Tsaloglou et al, 2018 ; Verma et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%